The development of visuo-spatial perspective taking in autism spectrum disorder - Pearson, Amy (2014)
The ability to take another person’s perspective is highly important for social interaction. People with autism have particular difficulty with taking someone else’s point of view. This thesis aimed to examine whether people with autism are impaired at visual perspective taking and the processes which underlie this ability and how this could impact on social interaction.